Presence of Ebola virus in breast milk and risk of mother‐to‐child transmission: synthesis of evidence. Issue 1 (28th October 2020) - Medina‐Rivera, Melisa; Centeno‐Tablante, Elizabeth; Finkelstein, Julia L.; Rayco‐Solon, Pura; Peña‐Rosas, Juan Pablo; Garcia‐Casal, Maria N.; Rogers, Lisa; Ridwan, Pratiwi; Martinez, Sabrina Sales; Andrade, Joyce; Layden, Alexander J.; Chang, Juan; et al.
Abstract: To help inform global guidelines on infant feeding, this systematic review synthesizes evidence related to the presence of the Ebola virus (EBOV) in breast milk and its potential risk of viral transmission to the infant when breastfeeding. We relied on a comprehensive search strategy to identify studies including women with suspected, probable, or confirmed EBOV infection, intending to breastfeed or give breast milk to an infant. Our search identified 10, 454 records, and after deduplication and screening, we assessed 148 full texts. We included eight studies reporting on 10 breastfeeding mothers and their children (one mother with twins), who provided breast milk samples for assessment. EBOV was detected via RT‐PCR or viral culture in seven out of ten breast milk samples. Four out of the five‐breastfed infants with EBOV‐positive breast milk were found positive for EBOV infection, and all of these EBOV‐positive infants died. Since previous reports have detected EBOV in tears, saliva, sweat, and contaminated surfaces, with the current evidence, it is not possible to conclude with certainty that breast milk was the main route of EBOV transmission. Abstract : Understanding maternal‐to‐child transmission routes is key to lowering, and ultimately preventing, the exposure of Ebola virus (EBOV) in pediatric populations. We undertook a systematic review of the available scientific literature to determine whether EBOV can be transmitted through breast milk and to describe the outcomes of the infants that ingested EBOV laboratory‐confirmed breast milk.